Optimization Selection Research of Chemical EOR Pilot Project Site for Umm Niqqa Oilfield in Kuwait. Issue 1 (January 2021) - Zhu, Hongzhang; Song, Mingming; Zuo, Qin; Zhang, Hong
Abstract: The Low Fars of Umm Niqqa oilfield in northern Kuwait is a carbonate formation. After many years of primary and secondary oil recovery, Kuwait Oil Company has started to use chemical EOR flooding technology to increase recovery in this reservoir in recent years, and plans to carry out chemical EOR Pilot project. Due to the dense well pattern and surface facilities in the oil field, the site selection of the pilot project has become a problem. This essay focuses on the optimization method of the pilot project site, underground influencing factors, surface influencing factors, and analysis of the preferred site. Therefore, several important conclusions for selecting the site of the pilot project are summarized: simplifying the site design, combining local geological conditions and construction experience of similar projects, will greatly reduce investment and improve the efficiency of the chemical flooding pilot project. The successful pilot site selection of Umm Niqqa water and polymer flooding pilot projects based on underground design and surface foundation includes well site selection and water source selection. Reserve the surrounding site in advance, drill new wells in this area, install and connect the corresponding water injection pipelines and manifolds to ensure the successful implementation of the chemical flooding pilot project.